2009
DOI: 10.3324/haematol.2009.014001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of myelodysplastic/myeloproliferative neoplasms

Abstract: Although the molecular characterization of these myeloid neoplasms is cumbersome in clinical settings, at least at present, the information provided by these studies is of crucial importance for defining their pathophysiology, and may ultimately lead to a molecular classification and a better prognostic definition of myelodysplastic/myeloproliferative neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
0
25
1
1
Order By: Relevance
“…Overall, these mutation frequencies are in line with published data, except for a slightly higher frequency of CBL mutations in CMML and the absence of NRAS mutations in MDS/MPN, U. [2][3][4][5]10,[12][13][14] In previous studies the frequency of the CBL mutation was found to be ~10% in CMML instead of the 24% in our study and RAS mutations were detected in 14% of MDS/MPN, U, contrasting with the 0% in the present study.…”
Section: 1011contrasting
confidence: 50%
“…Overall, these mutation frequencies are in line with published data, except for a slightly higher frequency of CBL mutations in CMML and the absence of NRAS mutations in MDS/MPN, U. [2][3][4][5]10,[12][13][14] In previous studies the frequency of the CBL mutation was found to be ~10% in CMML instead of the 24% in our study and RAS mutations were detected in 14% of MDS/MPN, U, contrasting with the 0% in the present study.…”
Section: 1011contrasting
confidence: 50%
“…Cytogenetics: clonal cytogenetic abnormalities in up to 80%; trisomy 8 and del(20q) are the most common, but abnormalities of chromosomes 13,14,17,19, and 12 are also commonly reported. 40 Molecular genetics: mutated NRAS, KRAS, or TET2 in nearly 30% 37 ; mutations of CBL, RUNX1, CEBPA, EZH2, or WT1 in 1%-10% 31,42,55 ; and JAK2 V617F occurs rarely if at all. 40 …”
Section: Disclosuresmentioning
confidence: 99%
“…13 In contrast, CSF3R was often mutated in CNL patients (43%, 6 of 14), but rarely in aCML and CMML cases, with only 2 patients each harboring a CSF3R mutation (3%, 2 of 58; 1%, 2 of 146). However, these 4 cases with CSF3R mutation in aCML and CMML showed neutrophil counts below 80% and increased monocyte numbers above 1000/mL in CMML cases and more than 10% neutrophilic precursors in aCML.…”
mentioning
confidence: 99%